Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $P$ is a $2n \times 2n$ real matrix satisfying $P^t J P = J$ where $J = \left(\begin{array}10 & I \\ -I & 0\end{array}\right)$ and if $P = Q S$ is the polar decomposition of $P$ then show that $Q$ and $S$ also satisfy

$$Q^t J Q = J \quad\text{and}\quad S^t J S = J.$$

Thanks for any help.

share|cite|improve this question
By ( 0 I -I 0 ) I meant the block matrix with diagonal entries nxn null matrix and the upper right entry the nXn identity matix and the lower left entry the additive inverse of the nxn identity matrix – Ester Oct 20 '12 at 15:59
Sorry everyone for the edits – Ester Oct 20 '12 at 16:02
up vote 1 down vote accepted

By definition $P$ is a real symplectic matrix and your question is called the polar decomposition for symplectic matrices.

Let $Q=\sqrt{PP^t}$. Then the matrix $Q$ is symmetric and positive definite. Now take $S=Q^{-1}P$ and check that $SS^t=I$, that is, $S$ is orthogonal. Moreover, this decomposition is unique: if $P=Q_1S_1=Q_2S_2$, then $Q_1^2=Q_2S_2S_1^tQ_1=Q_2^2$ and thus, by the uniqueness of the square root for positive symmetric matrices, we get $Q_1=Q_2$ and then $S_1=S_2$. (Nothing new so far: this is the polar decomposition of any invertible matrix.)

From $P^tJP=J$ we get $P=J^{-1}(P^t)^{-1}J$. By using that $P=QS$ we obtain $$P=J^{-1}(S^tQ)^{-1}J=(J^{-1}Q^{-1}J)(J^{-1}(S^t)^{-1}J).$$ The matrix $J^{-1}Q^{-1}J$ is symmetric and positive definite, while $J^{-1}(S^t)^{-1}J$ is orthogonal. By the uniqueness of the polar decompositon we obtain that $Q=J^{-1}Q^{-1}J$ and $S=J^{-1}(S^t)^{-1}J$, therefore $Q$ and $S$ are also symplectic.

share|cite|improve this answer
@ YACP As I can see, this problem with symplectic matrix is just transformation to polar, I have one more condition, how can I use this your answer and apply on mine problem… – Pipe Jul 17 '13 at 11:16

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.